Investigation of numerical model of Lenze 530 Dc drive in Matlab - Golodnyi, І.; Lawrinenko, Yu.; Toropov, A. (Lviv Polytechnic National University, 2014)
This paper describes DC drive with thyristor voltage regulator Lenze 530 series. To investigate the transients of the drive system developed numerical model in MatLab is developed. Dual circuit structural diagram of “TCV-DC motor” system with negative feedback for the current and angular speed or current and armature voltage in model is realized. By introduction of current feedback, torque and current limit are achieved and with using of armature voltage or tacho automatic speed stabilization is obtained. At this model certain standard settings of cascade control system are made. The basis of the internal loop consist from PI-regulator with KP.C=2 and KI.C=100 gains, TCV and armature transfer functions, covered by armature current feedback. Current controller is configured at technical optimum. Second circuit can have armature voltage feedback; can be tuned at technical optimum and has a P-regulator with KP.S=36 gain. In same way it can have a speed negative feedback with the same tunings. A numerical model has restrictive blocks: to limit the maximum and minimum speed and maximum current. To demonstrate the obtained results virtual oscilloscopes were used. Also the electromechanical characteristics of the drive with armature voltage and current or speed and current feedbacks using XYGraph block are presented. At this paper the electromechanical characteristic of the real DC drive Lenze 530 series is presented too. According to research results at numerical model and physical investigation equipment graphs of instantaneous values of current and electromechanical characteristics are made. Analysis of graphs confirms the adequacy of the results obtained at the numerical model and the real drive system, which enables the use of the developed numerical model for the investigation of similar DC drives. DC drive model with thyristor voltage regulator Lenze 534 and results of investigations of electromechanical properties are presented.
Keywords: transition process; semiconductor voltage converters; feedback; РІ-controls; electromechanical characteristics; model